Antifungal activity of a synthetic human β-defensin 3 and potential applications in cereal-based products. (December 2016) - Thery, Thibaut; Tharappel, James C.; Kraszewska, Joanna; Beckett, Michael; Bond, Ursula; Arendt, Elke K.
Abstract: Defensins are cysteine-rich antimicrobial peptides of the innate immune system involved in constitutive and adaptive immunities. The aim of this work was to characterize the antifungal activity of a linear human β-defensin-3 (HBD-3) and test this peptide as a potential food preservative. Antifungal activity of the synthetic HBD-3 was demonstrated against Fusarium culmorum, Penicillium expansum and Aspergillus niger . To determine potential baking applications with the defensin, a parental wild yeast Saccharomyces pastorianus strain, called CMBS-33, was transgenically modified. The novel lager yeast strain, called CM-INT-51, was able to express the gene encoding HBD-3. The use of CM-INT-51 to ferment the dough extends the shelf life of bread by three days in comparison to CMBS-33. Furthermore, synthetic HBD-3 (80 μg·ml − 1 ) delayed fungal growth on bread for > 13 days. These results revealed that both the synthetic peptide and the yeast containing HBD-3 have the potential to increase the shelf-life of baked goods. Industrial relevance: Fungal spoilage is an important cause of economic losses in the baking industry and might be a source of mycotoxins with detrimental effects on human health. Furthermore, the overuse of preservatives is subject to controversy. We showed that the linear analogue of HBD-3 displays antifungal activity against food contaminants in vitro and can be used to extend the shelf-life of bread. These results have direct applications to the baking and other related industries. Highlights: A novel synthetic antimicrobial peptide inhibits fungal growth. The recombinant yeast strain was able to produce the recombinant peptide in bread-making. Recombinant peptide extends the shelf-life of bread by 3 days.